SEDIMENT PARTICLE SELECTION DURING FEEDING BY FOUR SPECIES of UCA (BRACHYURA, OCYPODIDAE) - Colpo, K. D. [UNESP]; Negreiros-Fransozo, M. L. [UNESP] (Brill Academic Publishers, 2011)
Differences in sorting of sediment grain-size during the feeding activity of fiddler crabs were investigated experimentally in four Uca species that have different numbers of spoon-tipped setae on the second maxillipeds. Uca leptodactylus had the highest number of spoon-tipped setae, followed by Uca rapax and Uca thayeri; whereas Uca vocator had no setae of this type. The crabs were allowed to feed for 48 h, in containers filled with three types of sediments with different particle-size composition. The feeding pellets formed in each type of sediment were collected, and the proportion of each granulometric fraction was compared with the substrate in the container. The diameters of the sediment particles found in the crab stomachs were measured and compared among the species and the types of sediments. The granulometry of the feeding pellets in each substrate was similar among the species. The size of particles ingested by fiddler crabs reflected the granulometric composition of the experimental substrate. Only U. leptodactylus ingested the smallest grains in coarser sediments. Therefore, the variation in the number of spoon-tipped setae on the second maxilliped seems not to affect the ability of fiddler crabs to manipulate and sort different particle sizes during feeding.